(untitled) (The Research of Medical Science Review, 2025)
Background: Ureteroscopy stone treatment is used for removing ureteric stones. It is the recommended first therapy for the majority of ureteric stones. There is debate about the use of double-J (DJ) stents during URS stone removal. Objective: The aim of this study was to compare the Complications of Double J Stent and without Stent Following Ureteroscopy for Ureteric Stones. Material and method: The current case –control study was carried out at Institute of Kidney Diseases Hayatabad Peshawar from January 2023 to June A total of 60 individuals participated in this study. Each participant underwent Ureteroscopy for ureteric stones using lithoclast and a semi rigid Storz ureteroscope. Following the surgery, each individual was catheterized and maintained in the post-operative ward. Depending on the technique, the patients were randomly assigned to either the stented or non-stented group and was evaluated for the duration of the surgery, the need for post-operative painkillers, complications such as hematuria, dysuria, flank pain, lower abdominal pain, nocturia, frequency, and urgency during their hospital stay. After two weeks, all patients were evaluated with a follow-up Kidney Ureter Bladder Ultrasound (KUB) to record their stone-free status. SPSS software Version 16 was used for the statistical analysis. Results: Following ureteroscopic surgery, 60 participants who satisfied the eligibility requirements were randomly assigned to either the stented (cases) or non- stented (control) groups. There were 31 individuals in the non-stented group and 29 in the stented group. Stones obstructing the ureter at various points and ranged in size from 2 to 15 mm, with the mean diameters for the stented & non-stented groups being 11.3 and 9.9 mm, respectively. Compared to the non-stented group, the stented group’s operating time was longer. However, the mean duration of the hospital stay for both groups after surgery was two days, with no discernible difference in that time. Likewise, there were no statistically significant differences between the two groups in terms of patient gender, age, stone position, or average stone size. The stented group noticed a greater incidence of hematuria and dysuria than the non-stented group. Regarding further complications and consequences, there was not a noticeable distinction between the two groups. Conclusion: Our study concluded that as a standard treatment, postoperative Double J Stent following ureteroscopy for ureteric stones is not necessary. Participants in the non-stenting group suffer from less irritative symptoms, a lesser need for analgesics, and a lower financial burden.